ATRT-20. INTRA- AND EXTRA-CRANIAL MALIGNANT RHABDOID TUMOURS SHARE COMMON LOCATION-INDEPENDENT CLINICAL AND MOLECULAR DISEASE CHARACTERISTICS. Issue 2 (22nd June 2018) - Grabovska, Yura; Finetti, Martina; Selby, Matthew P; Schwalbe, Edward C; Smith, Amanda; Crosier, Stephen; Pickles, Jessica C; Fairchild, Amy R; Avery, Aimee; O'Hare, Patricia; Pizer, Barry; Brennan, Bernadette; et al.
Abstract: Atypical Teratoid/Rhabdoid Tumours (ATRT) are the CNS located members of a larger family of Malignant Rhabdoid Tumours (MRT); aggressive early childhood tumours characterised by biallelic inactivation of SMARCB1. ATRT and extra-cranial rhabdoid tumours (ECRT) are often treated as distinct entities therapeutically and in clinical/biological studies. We investigated to what extent this division is justified by the underlying molecular biology. RNA-Seq and methylation profiling of primary MRT was performed on 56 clinico-pathologically annotated tumour profiles from UK cancer centres and combined with published MRT data (n=394) in a meta-analysis. To characterise the common biological features of MRT regardless of location, differential expression, methylation, gene/pathway analyses were compared to other paediatric embryonal tumour expression (n=1073) and methylation (n=520) profiles (i.e. Medulloblastoma, Ewings Sarcoma, Rhabdomyosarcoma, Wilms tumour and Neuroblastoma). Clustering all MRT together recapitulates the subgroups observed in ATRT alone; broadly overlapping with recently published 3 ATRT subgroup models. We further describe a putative expanded subgrouping model encompassing all MRT. While expression, methylation, genetic and clinico-pathological differences by anatomical site are observed these are not innate but rather differences between ATRT and ECRT may be explained by differences in the molecular subgroup membership. We propose that anatomical site does not exclusively predetermine subgroup identity and that the overarching SMARCB1-dependent genetic, epigenetic and transcriptomic commonality is the "main event" in MRT tumorigenesis. Our findings demonstrate a need for common therapeutic approaches and targeting strategies across all MRTs, irrespective of location; these findings have important implications for clinical trial planning and future research studies.